2011
DOI: 10.1007/s00726-011-1094-9
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of intrathecal administration of hypotaurine in rat models of inflammatory and neuropathic pain

Abstract: Hypotaurine is an intermediate in taurine biosynthesis from cysteine in astrocytes. Although hypotaurine functions as an antioxidant and organic osmolyte, its physiological role in the central nervous system remains unclear. This study used behavioral assessments to determine whether hypotaurine influenced nociceptive transmission in acute, inflammatory, and neuropathic pain. The tail flick, paw pressure, and formalin tests were performed in male Sprague-Dawley rats to examine the effects of the intrathecal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Studies have indicated that hypotaurine was an antioxidant and a neurotransmitter influencing nociceptive transmission in vivo (Aruoma et al, 1988;Hara et al, 2011;Suzuki et al, 2007). Moreover, hypotaurine is a key intermediate in the taurine biosynthesis (Jerkins and Steele, 1992;Li et al, 2006;Ueki and Stipanuk, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Studies have indicated that hypotaurine was an antioxidant and a neurotransmitter influencing nociceptive transmission in vivo (Aruoma et al, 1988;Hara et al, 2011;Suzuki et al, 2007). Moreover, hypotaurine is a key intermediate in the taurine biosynthesis (Jerkins and Steele, 1992;Li et al, 2006;Ueki and Stipanuk, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…5′-Methylthioadenosine, is indeed now seen as a key regulator of immune responses to inflammation and systemic infections (Albers, 2009, Wang et al, 2017), proven to mediate protection against LPS-induced inflammation in vitro (Hevia et al, 2004), but also to inhibit inflammation and reduce brain damage in animal models of neuroinflammation (Moreno et al, 2006). Furthermore, hypotaurine which has well established antioxidant properties (Fontana et al, 2004), was also found to effectively suppress inflammatory and neuropathic pain (Hara et al, 2012). Taurine and hypotaurine are present in elevated levels in the brain of the long-lived Snell Dwarf mouse (Vitvitsky et al, 2013), which exhibits reduced oxidative damage to the brain (Brown-Borg, 2006) and hypothalamic inflammation (Sadagurski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this actions, animal studies reported anticonvulsive actions of taurine ( El Idrissi et al, 2003 ; El Idrissi and L’Amoreaux, 2008 ), which, however, were not completely replicated in humans (reviewed in Oja and Saransaari, 2013 ). In line with an inhibitory action in the spinal cord, taurine also has as a considerably antinociceptive effect ( Pellicer et al, 2007 ; Terada et al, 2011 ; Hara et al, 2012 ). In addition, taurine improves different in vitro correlates of memory formation ( Chepkova et al, 2002 ; del Olmo et al, 2003 ; Sergeeva et al, 2003 ) and accordingly augments learning and memory ( El Idrissi, 2008a ; Neuwirth et al, 2013 ).…”
Section: Introductionmentioning
confidence: 94%